Optimal Wildlife Corridor: A Review - Gautam, Nischal; Pradhan, Ratika (Indian Forester, 2020)
In the modern world where development is chosen over ecology, wildlife habitats are being continuouslysubjected to degradation, fragmentation, isolation or to global warming. Wildlife habitats are continuously becoming unsuitable for the sustenance ofwildlife including flora. Shrinkage of wildlife habitats and human wildlife conflicts are reciprocal across the globe. Isolation ofhabitats leads to genetic depression in species and ultimately the species gets extinct. Corridorhelps in movement of species and dispersal of genetic material which is ofprime importance for the ecosystem to survive and forits integrity. This paperpresents a review of many such papers published in the past in the area of corridors for wild animals and intends to find their properties; width, length or quality of the corridor which is best suited for wildlife for their sustenance and for their viable population. It is found that each species requires different environment but providing species specific requirement is difficult and hence the modern-day researchers are opting more for multi-species approach. However, as long as we lack full knowledge on wildlife corridor requirement, a rule of thumb of 2 Km width as proposed by Paul Beier in 2019 works well for 96% of the terrestrial mammals likely to be corridor dwellers.